The dynamic flow behaviour of an oar blade in motion using a hydrodynamics-based shell-velocity-coupled model of a rowing stroke - Sliasas, A.; Tullis, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
The flow around a rowing oar blade during a stroke is highly complex owing to the proximity of the water surface and the rapidly changing blade flow incidence (here, greater than 180° in under 0.75 s). This flow is simulated using a computational fluid dynamics (CFD) model with a rotating subdomain for blade rotation coupled to a model of the shell velocity. Based on the shell velocity and a specified oar angular velocity, the CFD model calculates the highly unsteady three-dimensional flow, providing instantaneous drag, lift, and propulsive forces on the blade. The propulsive force drives the shell velocity model, which also accounts for the shell drag and the motion of the rowers relative to the shell. The dynamic blade-water interaction is depicted in six distinct flow regimes, characterized by the relative motion of the blade and the temporal influence of drag and lift. It is seen that the propulsive force generated by the blade is largely lift induced during the first half of the stroke. Dynamic stall behaviour of the blade characterizes the flow during the second half of the stroke, where drag increasingly influences the propulsive force. At the end of the stroke, the propulsive force is once again largely lift induced.